Determining the Knowledge Levels of University Students About HPV and HPV Vaccine - Ayşe Dost; Arzu Torlak (Halk Sağlığı Hemşireliği Dergisi)
Objective: The purpose of this study is to determine the knowledge levels of university students about human papillomavirus (HPV) and the HPV vaccine. Methods: This descriptive study was conducted with 802 university students staying in the student dormitory of a foundation university on the Anatolian Side of Istanbul. The data of the study were collected using the "Student Information Form" and the "Human Papilloma Virus Knowledge Scale". Results: 16.5% of the participants had previous sexual experience, 5.1% had genital wart problems before, 15.8% had the HPV vaccine, the total score average of the "HPV Knowledge Scale" was 10.142±7.364 (Min:0-Max:33). When the sub-dimension mean scores are examined, the "general HPV knowledge" sub-dimension mean score is 6.657±4.276, the "HPV screening test knowledge" sub-dimension mean score is 1.029±1.316, the "general HPV vaccine knowledge" sub-dimension mean score is 1.591±1.737, the "current HPV knowledge" sub-dimension mean score is 1.591±1.737. The mean score of the "information about vaccination program" subscale was found to be 0.865±1.240. Conclusion: In this study, the level of knowledge about HPV and HPV vaccine among university students is quite low, and it is seen that this situation may affect general health awareness and protective behaviors.